Affective Experience on Social Networking Sites Predicts Psychological Well-Being Off-Line. Issue 5 (October 2019) - Shi, Yuanyuan; Luo, Yu L. L.; Liu, Yunzhi; Yang, Ziyan
Previous studies have pondered the relevance of social networking sites (SNSs) to psychological well-being, but few have taken online affective experience into consideration. To extend previous research on the relationship between SNSs and psychological well-being, we opted to target emotions experienced while visiting SNSs as a means to predict off-line well-being. In our two studies, we surveyed affective experience on SNSs, overall life satisfaction, and general emotional well-being of young adults who access SNSs regularly. The results consistently demonstrated a positive association between SNS affective experience and off-line well-being. This finding held with SNS activities (Studies 1 and 2) and relevant personality traits (i.e., the Big Five factors, self-esteem; Study 2) considered in simultaneity. Our research highlights the important role of affective experience on SNSs in predicting off-line well-being as well as helps clarify the relationship between SNSs and well-being.